The Influence Of Competency, Work Environment On Work Involvement And Job Satisfaction - Diah Pranitasari; Julian Julian (Jurnal Ilmiah Manajemen dan Bisnis, 2022)
This study aims to determine the competence and work environment on job involvement and job satisfaction of employees at PT. Yamaha Music Manufacturing Indonesia.The sample in this study was 100 contract employees, using purposive sampling technique. The analysis used is SEM PLS research to test the Inner model, outer model and hypotheses.The results of the study stated: (1) Competence has an effect on work involvement by 55.2%. (2) The work environment has an effect on work involvement by 39.1%. (3) Competence has an effect on job satisfaction by 36.2%. (4) The work environment has an effect on job satisfaction by 35.2%.